RANCANG BANGUN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN BUJANG DARE MENGGUNAKAN METODE TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) (Studi kasus : Dinas Kebudayaan dan Pariwisata Kota Pontianak ) - Sidoi, Leander (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2015)
Abstract-Tourism-based culture is a type of tourism activities that use its culture as an object.The application of tourism-based culture activities in Indonesia has been showed by the Department of Culture and Tourism of Pontianak.The tourism development is congruent with available potential which is centere don the culture that is consistent with the history and the culture of Pontianak City. In order to promote the history and the culture of Pontianak City which is needed tourism ambassador who had been selected in the Bujang Dare Selection.The purpose of this resear chis the testing of Bujang Dare proponent decision systemUsing TOPSIS method. The method use dis the method of Tecnique for Order Preference by Similarity to Ideal Solution (TOPSIS), applied in selecting the contestants of Bujang Dare Pontianak. The system can provide winners recommendation.The conclusions of this study, Bujang Dare Selection System with TOPSIS method can help the jurie store commend the winners of Bujang Dare Selection.The results of the respondents teston the conducted system, using Likert's method Summated Rating (LSR), the obtained scores is 202, it shows the respondents assess the system positively and considered successful.